INFLUENCE OF ARTIFICIAL INTELLIGENCE IN POWERING HRM - Britto, M. John; Magesh, R. (International Journal of Psychosocial Rehabilitation, 2020)
–Artificial Intelligence is gaining impetus day after day. artificial intelligence is not only being used in IT but has also found application in areas like Human resource management. This being the case, organisations have started seriously contemplating on deploying artificial intelligence solutions with respect to all the human resource functions. By using specialised software, HR professionals will be able to not find time to concentrate on important strategic issues. The objectives of this study are as to understand the of influence of artificial intelligence in powering HRM and to know the benefits expected from the use of AI in HRM.The results of the study have shown that HR professionals covered by the study have a long way to go before they can say that they are truly enjoying the full benefits of using AI in powering HRM.